TOBACCO LOBBY FIGHTS CIGARETES THAT GO OUT SAYS VICKERY (Tufts Archival Research Center, 2007)
Newspaper article on the proposed legislation requiring fire-safe cigarettes. Cites former Seattle Fire Chief Vickery, who claims that the tobacco industry is hostile. Explains the mechanisms of self-extinguishing cigarettes. Highlights the number of cigarette-related fire injuries each year.